Resistance to Cancer Treatment: The Role of Somatic Genetic Events and the Challenges for Targeted Therapies - Batist, Gerald; Wu, Jian Hui; Spatz, Alan; Miller, Wilson H.; Cocolakis, Eftihia; Rousseau, Caroline; Diaz, Zuanel; Ferrario, Cristiano; Basik, Mark (Frontiers in Pharmacology, 2011)
Therapeutic resistance remains a major cause of cancer-related deaths. Resistance can occur from the outset of treatment or as an acquired phenomenon after an initial clinical response. Therapeutic resistance is an almost universal phenomenon in the treatment of metastatic cancers. The advent of molecularly targeted treatments brought greater efficacy in patients whose tumors express a particular target or molecular signature. However, resistance remains a predictable challenge. This article provides an overview of somatic genomic events that confer resistance to cancer therapies. Some examples, including BCR-ABL, EML4-ALK, and the androgen receptor, contain mutations in the target itself, which hamper binding and inhibitory functions of therapeutic agents. There are also examples of somatic genetic changes in other genes or pathways that result in resistance by circumventing the inhibitor, as in resistance to trastuzumab and BRAF inhibitors. Yet other examples results in activation of cytoprotective genes. The fact that all of these mechanisms of resistance are due to somatic changes in the tumor’s genome makes targeting them selectively a feasible goal. To identify and validate these changes, it is important to obtain biopsies o